Brief online acceptance and commitment therapy for adults with type 1 diabetes: a pilot study - Stefanescu, Cristina; Tatu, Alin Laurentiu; Nechita, Aurel; Iacob, Claudia I.; Secara, Eugen; Nicolescu, Silvia; Huiu, Gabriela Alexandra (Frontiers in Clinical Diabetes and Healthcare, 2024)
Recognizing the pivotal role of psychosocial factors in triggering and maintaining Type 1 Diabetes Mellitus (T1DM), the integration of psychoeducational and psychotherapeutic interventions is associated with comprehensive management of the disease. This study aimed to evaluate the impact of a four-week online individual Acceptance and Commitment Therapy (ACT) intervention in mitigating diabetes-associated stress, fostering diabetes acceptance, enhancing the patient-doctor relationship, and promoting psychological flexibility in adults diagnosed with T1DM. Employing a single-arm trial design with mixed methodology, thirteen participants (Mage = 39.04, SDage =13.74) engaged in the intervention and completed self-report measures before and after the intervention. Quantitative analysis with the Wilcoxon signed-rank test indicated a statistically significant difference in diabetes-associated stress, diabetes acceptance, and psychological flexibility pre- and post-intervention. Notably, stress levels and psychological inflexibility diminished, while psychological flexibility and diabetes acceptance improved. However, the patient-doctor relationship did not exhibit a significant change. Furthermore, narrative feedback obtained from participants reflected overall satisfaction with the intervention. These preliminary findings contribute to the expanding body of literature supporting the affirmative influence of ACT interventions on individuals with T1DM.